PENELITIAN TINDAKAN KELAS DALAM PENDIDIKAN KEWARGANEGARAAN - T Heru Nurgiansah; Febri Fajar Pratama; Aulia Solichah Iman Nurchotimah (Universitas Tanjungpura, 2021)
ABSTRAKPenelitian Tindakan Kelas dilakukan untuk menyelesaikan permasalahan belajar. Guru yang profesional harus mampu mengaplikasikan beragam model dan media pembelajaran. Mayoritas siswa menganggap mata pelajaran Pendidikan Kewarganegaraan adalah yang paling membosankan. Tujuan penelitian adalah untuk melihat evaluasi tindakan yang dilakukan oleh guru Pendidikan Kewarganegaraan. Penelitian ini menggunakan metode kualitatif. Pengumpulan data menggunakan observasi, wawancara, dokumentasi, literasi.Kata Kunci: Penelitian Tindakan Kelas, Pendidikan Kewarganegaraan. ABSTRAKClass action research is conducted to solve learning problems. Professional teachers must be able to apply various models and learning media. The majority of students consider civic education subjects to be the most tedious. The purpose of this research is to know the successful research of class actions conducted by the teachers of citizenship education. This research uses qualitative methods. Data collection using observations, interviews, documentation, literacy. The results of this research show that the teachers of citizenship education who conduct class action research successfully solve learning problems such as low motivation and student achievement while ensuring that class action research is a concrete solution in the course of learning problems especially in citizenship education subjects. Kata kunci: Penelitian Tindakan Kelas, Pendidikan Kewarganegaraan.